Correlation between IL-3 receptor expression and growth potential of human CD34+ hematopoietic cells from different tissues - Huang, Shiang; Chen, Zhang; Yu, Ji Feng; Young, Dennis; Bashey, Asad; Ho, Anthony Dick; Law, Ping (Stem cells, 1999)
CD123 (α-subunit of IL-3 receptor) expression on primitive and committed human hematopoietic cells was studied by multicolor sorting and single-cell culture. The sources of cells included fetal liver (FLV), fetal bone marrow, umbilical cord blood, adult bone marrow and mobilized peripheral blood. Three subsets of CD34+ cells were defined by the levels of surface CD123: CD123negative, CD123low, and CD123bright. Coexpression of lineage markers showed that a majority of CD34+CD123bright cells were myeloid and B-lymphoid progenitors, while erythroid progenitors were mainly in the CD34+CD123negative subset. The CD34+CD123low subset contained a heterogeneous distribution of early and committed progenitor cells. Single CD34+ cells from the CD123 subsets were cultured in a cytokine cocktail of stem cell factor, interleukin 3 (IL-3), IL-6, GM-CSF, erythropoietin, insulin-like growth factor-1, and basic fibroblast growth factor. After 14 days of incubation, a higher cloning efficiency (CE) was observed in the CD34+CD123negative and CD34+CD123low fractions (37 ± 23% and 44 ± 23%, respectively) than in the CD34+CD123bright fraction (15 ± 21%). Using previously published criteria that colonies containing dispersed, translucent cells (dispersed growth pattern, DGP) were derived from primitive cells and that colonies composed solely of clusters were from committed cells, early precursors were distributed evenly in the CD34+CD123negative and CD34+CD123low subsets. When CD38 and CD90 (Thy-1) were used for further characterization of CD34+ cells from FLV, CE increased from 37 ± 23% in CD123negative to 70 ± 19% in CD123negativeCD38− and from 44 ± 23% in CD123low to 66 ± 19% in CD123lowCD38−. No significant increase in CE or DGP progenitors was observed when CD34+ cells were sorted by CD90 and CD123. We concluded that: A) high levels of CD123 were expressed on B-lymphoid and myeloid progenitors; B) early erythroid progenitors had little or no surface CD123, and C) primitive hematopoietic cells are characterized by CD123negative/low expression.
Gesehen am 10.12.2021